2017
DOI: 10.1371/journal.pone.0175527
|View full text |Cite
|
Sign up to set email alerts
|

Filthy lucre: A metagenomic pilot study of microbes found on circulating currency in New York City

Abstract: BackgroundPaper currency by its very nature is frequently transferred from one person to another and represents an important medium for human contact with—and potential exchange of—microbes. In this pilot study, we swabbed circulating $1 bills obtained from a New York City bank in February (Winter) and June (Summer) 2013 and used shotgun metagenomic sequencing to profile the communities found on their surface. Using basic culture conditions, we also tested whether viable microbes could be recovered from bills.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…We found more frequently the presence of potentially pathogenic S. aureus, Acinetobacter, Pseudomonas, Bacillus cereus or Neisseria flavescens in case of more than one percent of E. faecalis DNA compared to less than one percent in total bacterial 16S rRNA of studied 27 mobile phones (10/15 vs. 3/12, respectively; p=0.031). The non-pathogenic skin microbe M. luteus frequently found in large amounts on circulating currencies 20,21 was also found more frequently on phones with more than one compared to less than one percent (11/15 vs. 4/12, respectively; p=0.038) of E. faecalis DNA (Table 1). Although in our study an evaluation of the health condition of schoolchildren was not addressed, E. faecalis appeared to be a good environmental contamination indicator.…”
mentioning
confidence: 99%
“…We found more frequently the presence of potentially pathogenic S. aureus, Acinetobacter, Pseudomonas, Bacillus cereus or Neisseria flavescens in case of more than one percent of E. faecalis DNA compared to less than one percent in total bacterial 16S rRNA of studied 27 mobile phones (10/15 vs. 3/12, respectively; p=0.031). The non-pathogenic skin microbe M. luteus frequently found in large amounts on circulating currencies 20,21 was also found more frequently on phones with more than one compared to less than one percent (11/15 vs. 4/12, respectively; p=0.038) of E. faecalis DNA (Table 1). Although in our study an evaluation of the health condition of schoolchildren was not addressed, E. faecalis appeared to be a good environmental contamination indicator.…”
mentioning
confidence: 99%
“…This study reveals new findings that will guide authorities, banks and the Fintech industry to point out the importance of using digital financial services instead of traditional methods. The study also revealed the most important finding, which is the following: Fintech perception and behavior (Fintech Behavior before COVID-19, Fintech Behavior after COVID-19, and Fintech Perception after COVID- 19) have the greatest impact on and association with predicting the spread of COVID-19 among people (52.5%). People think that avoiding physical contact with cash and any payment tools or methods helps reduce the spread of COVID-19 by changing their financial behavior, especially during the pandemic, toward using electronic and contactless payment methods.…”
Section: Resultsmentioning
confidence: 82%
“…To control the outbreak, it is pertinent to identify the potential source of infection in community, characterize the route and break the chain of transmission. Like other fomites, banknote is an ideal source of pathogenic microbes (Gabriel et al, 2013; Hiko et al, 2016; Jalali et al, 2015; Maritz et al, 2017; Pal and Bhadada, 2020; Thomas et al, 2008). Microbes remain infective in papers, stability depends on initial loads, temperature, and moisture content of the surrounding environment (Pastorino et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%